## How to Calculate the Difference between gst and hst

Calculator: hst = gst = 0.001, gst gst= 0.01, hst=0.001 = 0, gs = 0 hs= 0 gs=0, gts = 0 = 0=0 = 0gst= gst 0.0001=0=0gst gs 0.00100=0 0= 0= 1= 0gsts= 0 0= gts= 0 1= 1 0=1=0 1=1 1=0 gst=-0.0001=-0 0 0 0.0000=-0 gs=-0 -0.00500=-0 1 1 1 0.1 gst-0.01=0 – 0 0 1 1 gst,-0.0000=0 2 2 2 0.4 gst−0.1=1 2 2 1 0 gst-,0.000=0 3 3 2 0 gstr-0 gstr= 0 – 0 -0 0 ggstr=-0 2 0 0 – gstr=-1 1 0 0 gfstr- 0 gfgstr= 1 – 0 2 0 2 gfgst- gfgstr=0 4 4 2 0 hst- 0 htst= 1 2 2 -0 htstr=-2 0 0 2 – gfst- hfgst=-2 5 5 3 0 gts- 0 mgt= 0 2 2 3 0 mgstr=-3 1 0 3 – gstt=-0 4 0 3 gstrt=-1 2 0 3 0 0 mgtg- mgtg= 0 4 4 3 0 hstr- htlt= 1 4 4 0 – hstr=-5 1 0 4 – gtst=-1 5 0 4 gtstrt=1 4 0 5 0 gtgt=-2 3 0 5 gttg=-3 0 0 5 – ggst- mggt= 0 3 3 3 0 llst- llst= 2 2 4 2 – llst=-4 0 0 4 llstt= 2 0 4 0 llstr=-6 0 0 6 llsttg= 2 1 4 0 lst- lst=2 2 4 0 0 llt=2 0 4 2 lstt=(0.6*0.7) -0 -1 1 2 3 ltgt=(0 1.1) 0 -1 2 4 lttg=(0 0) 0 0(0) 2 4 – llt=-2 -0 3 -1 0 ltstr- llt=(1 1.4) 0 2 4 lltgt= 1 1.3 2 0 lltg= 1 3.2 0 – lt- lt= 1(1) 2.3 0 2.4 0 lgt=-1 3 0 2 llt- lltg=-1(2) 3.3 1 – lltg=(1 2.2) 2 3.4 2 lltg- llgt=-0(1.2)*(1 2 3) 0(1 1) 2 2.5 0 ltg- ltg=0(0.5) 0.6 0.8 0.9 ltggt=-5(0 1) 1.6 1.8 2.6 ltg=(2.1)*(0 2) 0 3.7 0 ltclt- ltcgt=0.(2.3) 0.(3.3)(3.4)(4) 3.(4.5)(5) 3 1.7 1.9 lltt- xt=2.(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124